2015
DOI: 10.1007/s40273-015-0313-8
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Falls and Injury Prevention Strategies for Older Adults Living in Residential Aged Care Facilities

Abstract: The model suggests that vitamin D supplementation and medication review are cost-effective interventions that reduce falls, provide health benefits and reduce health care costs in older adults living in RACFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 38 publications
0
36
0
1
Order By: Relevance
“…Four economic evaluations of medication adjustment programs were identified . Two reported the ICERs of CUAs on medication review or withdrawal and showed that it was cost saving in a population of older adults living in a residential care facility . One showed that the program was cost‐effective in community‐dwelling older adults .…”
Section: Resultsmentioning
confidence: 99%
“…Four economic evaluations of medication adjustment programs were identified . Two reported the ICERs of CUAs on medication review or withdrawal and showed that it was cost saving in a population of older adults living in a residential care facility . One showed that the program was cost‐effective in community‐dwelling older adults .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, between 2005 and 2013 in Suffolk County, the median incidence rate of falls in patients age ≥65 who were treated and released from the ED was 3,792 (IQR 3,527–4,056) per 100,000 population; a further 2,293 (IQR 2,128–2,251) were hospitalized (with or without a corresponding ED visit) per 100,000 population . Enrollment of older adults in fall prevention programs would appear indicated …”
Section: Discussionmentioning
confidence: 99%
“…20 Enrollment of older adults in fall prevention programs would appear indicated. 21,22 A key finding of this 10-year study was that 18% of older adults who were admitted after falling from a low-level sustained a spinal fracture; if sacrococcygeal fractures are excluded then 11% sustained a cervicothoracolumbar spine fracture. A variety of methodologic issues likely explain the substantially higher frequency of spinal fractures in our study than the 0.6% incidence in a NTDB study that examined patients throughout the United States, e.g., differing inclusion criteria and imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…11 Other interventions to reduce falls-or mitigate their impact-such as vitamin D supplementation and hip protectors may also be cost effective. 12 Whether these interventions are best targeted at the worst 2% (however identified) is unknown. It is possible they would be better targeted at less frail patients.…”
mentioning
confidence: 99%